Effects of drought and salt stress on seed germination of ephemeral plants in desert of northwest China - Lu, Yuting; Liu, Huiliang; Chen, Yanfeng; Zhang, Lan; Kudusi, Kawushaer; Song, Jihu (Frontiers in Ecology and Evolution, 2022)
Seed germination is the most sensitive stage of plant life history. Studying its response to drought and salinity can analyze the response and adaptation characteristics of desert plants to the environment. In this experiment, the seeds of four common desert ephemeral plants in Xinjiang (Ixiolirion tataricum, Nepeta micrantha, Lepidium apetalum, and Plantago minuta) were used as materials. To study the germination characteristics of seeds under drought, we used salt stress, and coupled salt-drought stress under treatments and explored the germination recovery ability of rehydrated seeds after salt and drought stress treatments. The results showed that: (1) The germination nodes of the four plant seeds were delayed, and the germination process was slowed as the NaCl concentration increased. Their ability to germinate was inhibited to different degrees, and the degree of inhibition was generally proportional to the concentration of NaCl solution. (2) Drought stress slowed the seed germination process, and the greater the degree of stress, the more pronounced the slowdown; PEG treatment showed no significant effect on the germination of the four seeds at low concentrations and significant inhibition at medium and high concentrations. (3) The coupled salt-drought treatment significantly alleviated the stress effect of one factor and improved the germination characteristics of seeds. (4) Seeds that did not germinate under different concentrations of salt stress, drought stress, and coupled stresses rapidly recover germination when the stress is relieved or lifted. Ephemeral plants are sensitive to environmental changes, and this study aims to provide a reference basis for vegetation restoration and ecological rehabilitation in arid and semi-arid areas.